Monitoring and analysis of carbon monoxide and methane using Sensors and Remotely Piloted Aircraft Systems - Holgado-Apaza, Luis Alberto; Julian-Laime, Edgar; Baca, Justo Bautista; Castillo, Ralph Miranda; Prieto-Luna, Jaime Cesar; Córdova-Mendoza, Pedro; Zea, Norberto Sixto Miranda; Valles-Coral, Miguel (EAI Endorsed Transactions on Energy Web, 2023)
INTRODUCTION: Air pollution in urban areas becomes a severe challenge to global health; exposure to polluting gases can lead to different diseases and even human mortality. In this sense, monitoring the concentration of polluting gases such as carbon monoxide and methane is important. OBJECTIVES: This document focuses on developing a Remotely Piloted Aircraft System (RPAS) to monitor the concentration of carbon monoxide and methane at different altitudes. METHODS: This includes a Parrot AR Drone 2.0, where the measurement prototype was mounted. The data was transmitted and reception at a ground control station through an application programmed in LabVIEW 15.0. RESULTS: The experimental measurements showed that the concentration of carbon monoxide remains almost unchanged regardless of variations in altitude. In contrast, methane concentration reduces linearly with the increase in height with respect to ground level in Puerto Maldonado. CONCLUSION: We implemented an RPAS to monitor in real time, record data in a control station and analyze the concentration of carbon monoxide and methane in the South Eastern Peruvian Amazon.